The relationship between absolute and relative upper-body strength and handcycling performance capabilities - Nevin, J.; Smith, P. M. (International Journal of Sports Physiology and Performance, 2021)
Purpose: To explore the relationship between absolute and relative upper-body strength and selected measures of handcycling performance.